Adaptation and reliability of tests of functional mobility and muscle strength using telehealth for older people with dementia - Carolina Tsen; Paulo Henrique Silva Pelicioni; Jéssica Bianca Aily; D. Moyano Bueno; Renata Carolina Gerassi; Juliana Hotta Ansai; Grace Angélica de Oliveira Gomes; Larissa Pires de Andrade (2024)
Objective: Adapt functional mobility and muscle strength tests for older people with dementia to be performed remotely in the home environment; determine intra-rater and inter-rater reliability of functional mobility and strength tests for older people with dementia; and correlate the performance on the physical tests executed remotely and the Timed Up and Go (TUG) test, which was validated remotely in healthy older people. Methods: We included 43 people with dementia. The Short Physical Performance Battery (SPPB), TUG, TUG Dual Task (TUG-DT), and 30-Second Sit-to-Stand Test (SST30s) were performed through videocalls. Test performance was documented to facilitate the subsequent determination of inter- and intra-rater reliability. The intra-rater reliability was determined at a 2-week interval from the real-time videocall to analysis of the recording. Results: Intra-rater reliability ranged from good to excellent for all tests performed (ICC 0.862–1.000). Inter-rater reliability values were fair for gait speed (ICC = 0.223), moderate for some of the SPPB items (ICC = 0.706–0.801), good for the SPPB two-foot balance (ICC = 0.860) and the SPPB total score (ICC = 0.831), and excellent for the rest of the tests. Conclusion: Functional mobility and muscle strength tests proved reliable and feasible for remote, at-home assessments of older people with dementia when assisted by their respective caregivers, providing an additional alternative for assessment of this patient population.